2011
DOI: 10.1002/smi.1308
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and dorsolateral prefrontal cortex volume in corticosteroid‐treated patients given lamotrigine

Abstract: In addition to changes in declarative memory and the hippocampus, corticosteroid excess is associated with prefrontal cortex changes. We previously reported that patients receiving exogenous corticosteroid therapy had impaired performance on prefrontal cortex‐related tasks, including working memory and executive functioning tasks. Glutamate release inhibitors attenuate corticosteroid‐effects on the hippocampus in both animal and human models. Twenty‐eight outpatients receiving chronic prednisone therapy for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Since the left DLPFC had been selectively activated during the high conflict of the SCWT trials, 35 this had thus demonstrated a higher left DLPFC activation through the coordinated recruitment of brain systems and, consequently, a higher cognitive skill was observed among the subjects with higher ulam consumption. 36 Although the right DLPFC activation had not been significantly associated with ulam consumption, its activation could have been due to the macro-adjustments of the cognitive control, which minimized the subsequent attentional conflict during the frequent congruent and incongruent SCWT. 23 The sample size of this study was also calculated and justified sufficiently, where the investigation on the association between ulam consumption and brain activation had been successfully conducted through the use of the fMRI; hence, corresponding to several previous studies that were conducted on the nutrients intake and brain activation with a small sample (n = 15-30).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the left DLPFC had been selectively activated during the high conflict of the SCWT trials, 35 this had thus demonstrated a higher left DLPFC activation through the coordinated recruitment of brain systems and, consequently, a higher cognitive skill was observed among the subjects with higher ulam consumption. 36 Although the right DLPFC activation had not been significantly associated with ulam consumption, its activation could have been due to the macro-adjustments of the cognitive control, which minimized the subsequent attentional conflict during the frequent congruent and incongruent SCWT. 23 The sample size of this study was also calculated and justified sufficiently, where the investigation on the association between ulam consumption and brain activation had been successfully conducted through the use of the fMRI; hence, corresponding to several previous studies that were conducted on the nutrients intake and brain activation with a small sample (n = 15-30).…”
Section: Discussionmentioning
confidence: 96%
“…The latest evidence therefore reported the left hemisphere of the human brain as being more affected by the interference than the right hemisphere when naming the color of a word that conflicted with the displayed word (eg, the word "yellow" printed in "orange"). Since the left DLPFC had been selectively activated during the high conflict of the SCWT trials, this had thus demonstrated a higher left DLPFC activation through the coordinated recruitment of brain systems and, consequently, a higher cognitive skill was observed among the subjects with higher ulam consumption . Although the right DLPFC activation had not been significantly associated with ulam consumption, its activation could have been due to the macro‐adjustments of the cognitive control, which minimized the subsequent attentional conflict during the frequent congruent and incongruent SCWT …”
Section: Discussionmentioning
confidence: 99%